The Impact of Entrepreneurial, Financial, and Digital Literacy on MSME Performance - Besse Wediawati; Zulfina Adriani; Rike Setiawati; RTS. Ratnawati; Erwita Dewi (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study investigates the influence of entrepreneurial, financial, and digital literacy on micro, small, and medium enterprise (MSME) performance, with microfinance acting as a moderating factor. Conducted among 158 MSMEs partnered with Islamic microfinance institutions in Jambi Province, Indonesia, the research adopts a quantitative approach using Partial Least Squares (PLS) to test the proposed model. The findings confirm that all three types of literacy significantly and positively affect business performance, with entrepreneurial literacy showing the strongest influence. Despite financial literacy being only moderately high and digital literacy still relatively low, both remain important predictors of improved business outcomes. Notably, microfinance plays a key moderating role by enhancing the impact of these literacies on performance, emphasizing its role beyond financial support toward capacity-building and knowledge empowerment. The results suggest that improving the literacy of microfinance managers and building partnerships with stakeholders, universities, and digital communities are crucial steps toward strengthening MSME resilience and competitiveness. This study contributes a novel empirical model from the perspective of micro-entrepreneurs, offering a foundation for future research that explores microfinance and MSME dynamics from both demand and supply perspectives to better support business sustainability in the digital economy.